CHILDHOOD FEATURES IN THE CARTOONS OF THE ARTIST JUAN MIRO - Sukaina Hasan Khayif (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The current research dealt with (Childhood features in the drawings of the artist Juan Miro ), where the research contained four chapters. The first chapter included presenting the research problem that dealt with the following question: What are the childish features in Juan Miro's drawings? The first chapter also contained a presentation on the importance of research and the need for it, as well as the aim of the research to identify the characteristics of childhood in the drawings of Juan Miro, and while the limits of the research are limited to studying the drawings executed in the period between (1923 - 1978) as well as the most important terms mentioned in the research. The second chapter included the theoretical framework and display indicators of the theoretical framework, which included two sections, addressed the first topic : childhood features in the drawing, and the second section has included themes childish shapes in Juan Miro fees, while the third chapter included research procedures by addressing community The research and its sample of (5) is a work of art, which was intentionally chosen according to the justifications, justifications and needs of the aim of the research . As for the research tool, it relied on criteria derived from the indicators of the theoretical framework, in addition to recommendations and proposals. Among the most prominent results that the researcher reached are: The childish visions varied in the works of the artist (Juan Miro), within a number of attempts, divided between the style and technique of the surrealist movement and the artist's abstract style of painting. Most of the artist (Miro's) productions were characterized by the simplicity of shapes and free expression as children express, and with high spontaneity and spontaneity, by using what was stored in his memory since childhood.